The Eucharist as the foundation of the radical newness of man - Warchoł, Paweł (Studia Teologiczne Białystok Drohiczyn Łomża, 2021)
The power and strength of the Eucharist instituted by Jesus in the Upper Room is food for people who want to live God's life. Those who embark on this path experience the newness of life by rejecting sin and following Jesus. Therefore, the Upper Room is the place where we find the various stages of the inner transformation of man. From the washing of the feet of the apostles, through the supper and consecration of the bread and wine that became Christ's Body and Blood, to receiving the Holy Spirit, there are stages of inner transformation. This is evidenced by the wealth of gestures and words of Jesus, in which we find encouragement to understand and implement them in our lives.